Morphological variations of green peach aphid Myzus persicae (Sulzar 1776) (Hemiptera: Aphididae) from different areas of Iraq - Al-Kallabe, Haidar H.; Mohammed , Akram A.; Kareem, Ali A. (Journal of Kerbala for Agricultural Sciences, 2023)
The green peach aphid, Myzus persicae is one of the most harmful agricultural pests worldwide. Therefore, understanding the morphological variations among populations are important for the management of this pest. samples were collected from 11 locations in Iraq to compare among ten characteristics of collected populations. The most important differentiation characteristics are the length of the antenna, body, mouth parts and femur. The antenna length was greater in the aphids which collected from North areas of Iraq; however, the length of the body was greater in the aphids from locations in the mid of Iraq. the length of mouth parts was larger among the aphids collected from southern locations. Current results offer more evidence suggesting that there may be more than one genotype of M. persicae in Iraq. However, further studies on the genetic variations among collected populations are required.